Association of hydromyelia and acute compressive myelopathy caused by intervertebral disc extrusion in dogs. (28th April 2022) - Johnson, Philippa J.; Todd‐Donato, Amy B.; Miller, Andrew D.; Wang, Yu; Holm, Chris; Panisello‐Manterola, Carolina I.; Colón Acevedo, Claudia S.; Wood, Jonathan H.
Abstract: Background: Hydromyelia is a common magnetic resonance imaging (MRI) finding associated with compressive myelopathy caused by intervertebral disc extrusion (IVDE). Objectives: To describe the MRI features of hydromyelia and explore its relationship to clinical history, neurological severity, and the duration of cord compression. Animals: Ninety‐one client‐owned dogs with a focal compressive myelopathy secondary to thoracolumbar IVDE. Methods: A retrospective observational study was conducted in which MRIs were blindly evaluated to grade and localize hydromyelia and measure the degree of spinal cord compression. Duration and severity of clinical signs were recorded. Differences between hydromyelia grades in these variables were statistically assessed using a Wilcoxon and Kruskal Wallis test. Receiver operator curve analysis was used to determine the sensitivity and specificity for duration of clinical signs to predict the presence of hydromyelia. Results: Hydromyelia was identified at sites of IVDE in 84 of 91 dogs. An absence of hydromyelia was associated a with statistically longer duration of clinical signs (mean 73.1, IQR 76 days) when compared to cases with mild (mean 17.7, IQR 7.25 days, P  = .006) or severe (mean 17.9, IQR 10.25 days, P  = .006) hydromyelia. Duration of clinical signs <14 days was 78.6% sensitive and 85.7% specific for predicting the presence of hydromyelia. Conclusions and Clinical Importance: The MRI finding of hydromyelia might be a predictor of lesion chronicity in focal IVDE, helping to guide planning of hemilaminectomy surgery.